PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN MEKANISME PERTAHANAN DIRI SISWA KELAS VIII SMP TRI BHAKTI PEKANBARU T.P 2015/2016 - Ade, Nidya Muthia Sari; Yakub, Elni; ', R.Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find the influence of group guidance service to the decline of self defense mechanisme of the students. This type of research is quasi experiment with one group pre test and post test pattern. Analysis used in this research is descriptive qualitative and quantitative analytic. Subjects in this study were selected using non probability sampling technique with purposive sampling method. This research research is 30 people, this data collection method is questionnaire. Group guidance on Self Defense mechanisme decline 26% in the mean, while 74% influenced by variables or other factors such as environment, school, family.Keywords : Group Guidance Services,Self Defense Mechanisms